Trade unions in an emerging economy: The case of South Africa - Haroon Bhorat; Karmen Naidoo; Derek Yu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper provides a historical overview of the South African trade union movement, followed by a brief discussion of the labour market legislation and institutions formed since 1994. Thereafter, a detailed evaluation of the impact of trade unions, legislation, and institutions on labour market outcomes in South Africa is provided, and it is found that despite a long history, trade union membership levels, their impact on average wage levels, and their pursuit of strike action, has resulted in relatively benign economic impacts within country and relative to other economies around the world. The political-economy effects shaping the country's employment relations are then discussed.
Keywords: F50; J30; J51; J52; 330; trade unions; labour market efficiency; wage premium; strikes; political economy; South Africa